The mediator role of psychological morbidity on sleep and health behaviors in adolescents - Silvia Helena Modenesi Pucci; Maria da Graça Pereira (Brazilian Society of Pediatrics, 2016)
Objective: This study examined the mediation role of psychological morbidity, defined in this study as depression/anxiety, in the relationship between excessive daytime sleepiness and sleep quality, and between sleep habits and health behaviors, in adolescents. Methods: A total of 272 students, between 12 and 18 years old, underwent a psychological protocol assessing excessive daytime sleepiness, sleep quality, sleep habits, health behavior, and psychological morbidity. Results: Psychological morbidity was not associated with the relationship between excessive daytime sleepiness and sleep quality, but was associated, with statistical significance, in the relationship between sleep habits and health behaviors. These results emphasize the role of psychological morbidity in adolescent health behaviors. Conclusion: Analyzing the symptoms of depression and anxiety in pediatric patients may help in a more accurate diagnosis, especially in relation to sleep problems and health behaviors.